Pengaruh Love of Money dan Hedonisme terhadap Pengelolaan Keuangan Mahasiswa: Fintech Payment Sebagai Moderator - Berutu, Ronesa Muliana; Puspita, Lisa M N (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This study aims to analyze the effect of love of money and hedonic lifestyle on the financial management skills of accounting students, by considering the moderating role of the use of fintech payments. The approach used is quantitative, with purposive sampling technique. Data were collected from 400 respondents of accounting students in Indonesia through questionnaires. The analysis was carried out using the Partial Least Square (PLS) method with the help of the SmartPLS application. The test results show that love of money has a positive and significant influence on student financial management (coefficient = 0.270; T-statistic = 7.225; P-value = 0.000). In contrast, hedonism has a significantly negative impact on the ability to manage finances (coefficient = -0.208; T-statistic = 5.073; P-value = 0.000). The use of fintech payment also proved to have a positive and significant effect (coefficient = 0.555; T-statistic = 10.951; P-value = 0.000). In testing the moderating effect, it was found that the interaction between fintech payment and love of money has a significant effect on financial management (T-statistic = 3.917; P-value = 0.000), which means that fintech strengthens the positive influence of love of money. In addition, the interaction between fintech payment and hedonism is also significant (T-statistic = 4.608; P-value = 0.000), indicating that fintech is able to weaken the negative influence of hedonism. These findings may contribute to improving financial literacy and management.